In Vivo Ultrasound Molecular Imaging of SDF-1 Expression in a Swine Model of Acute Myocardial Infarction - Wang, Meng; Hu, Rong; Yang, Yuanyuan; Xiang, Liping; Mu, Yuming (Frontiers in Pharmacology, 2019)
Background: Stem cell therapy of acute myocardial infarction is proving to be a promising approach to repair the injured myocardia. However, the time window for stem cell transplantation is important and yet difficult to determine since it produces much different therapeutic effect at different times after myocardial infarction. Stromal cell-derived factor-1 (SDF-1) plays a pivotal role in the mobilization, homing, proliferation and differentiation of transplanted stem cells. Here, by using of ultrasound molecular imaging via targeted microbubbles, we determined the dynamic expression of SDF-1 in a swine model of acute myocardial infarction (AMI) in vivo. Methods: Twenty-four miniswine were randomly selected for the control group and AMI model group which underwent ligation of the left anterior descending coronary artery (LAD). There AMI animals were randomly divided into the six experimental groups according to the duration of the myocardial infarction. All animals were performed with ultrasound molecular imaging through injecting with targeted microbubbles (T + T group) or non-targeted control microbubbles (T + C group). The values of the myocardial perfusion parameters (A, β, and A × β) were determined using Q-Lab (Philips ultrasound, version 9.0) and the expression level of SDF-1 was analyzed by RT-PCR. Results: Our results showed that the expression of SDF-1 was gradually increased and peaked at 1 w after AMI. The trend can be well reflected by ultrasound molecular imaging in the myocardial perfusion parameters. The A, β, and A× β values were correlated with SDF-1 in the T + T group (r=0.887, 0.892, and 0.942; P<0.05 and P<0.01). Regression equations were established for the relations of the A, β, and A × β values (X) with SDF-1 (Y): Y=0.699X - 0.6048, Y=0.4698X + 0.3282, and Y=0.0945X + 0.6685, respectively (R2=0.772, 0.7957, and 0.8871; P <0.05 and P < 0.01). Conclusions: Our finding demonstrated ultrasound molecular imaging could be used to evaluate the expression dynamics of SDF-1 after AMI.